PENGARUH SANKSI PERPAJAKAN, TARIF PAJAK DAN PENERAPAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS DI KPP CEMPAKA PUTIH) - Ariska Noviyanti; Saprudin Saprudin; Sita Dewi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2020)
This study aims to determine the effect of tax sanctions, tax rates, and the application of e-filling on individual taxpayer compliance. This type of research is quantitative. This research was conducted at KPP Pratama Cempaka Putih Jakarta. The population in this study were 71,787 taxpayers registered at Cempaka Putih White Tax Office. The sampling technique in this study was using random sampling and the number of samples obtained was 100 individual taxpayers. Data collection techniques using a questionnaire. The data used in this study is in the form of primary data. The data analysis technique used is multiple linear analysis. The results of this study indicate that tax penalties, tax rates and the application of e-filling have a positive effect on the compliance of individual taxpayers.